Partial Replacement of Wheat Bran with Tea (Camelia assamica) Waste in Weaner Soviet Chinchilla Rabbits Diets: Effect on Nutrient Utilisation and Performance - Das, Chandralekha; Saikia, B.N.; Phukan, B.; Baruah, K.K.; Joysowal, M. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to study the effect of factory tea (Camellia assamica) waste on the performance of Soviet Chinchilla rabbits. Twenty four, 42 day old (12 male + 12 female) Soviet Chinchilla rabbits of average body weight of 1056 g were divided into 4 groups of 6 animals each. Four experimental rations wereprepared containing 0, 5, 10 and 15% tea waste replacing wheat bran in groups E1, E2, E3 and E4, respectively and fed a small amount of para grass for a period of 42 days Average daily gain of 20.93, 20.44 20.28 and 13.88 g with feed /gain ratio of 3.57, 3.55, 3.39 and 4.11 was found in groups E1, E2, E3 and E4, respectively. The digestibility of DM, CP, EE, CF and NFE was lower (P